COMPARATIVE ANTIFUNGAL STUDY OF FLUCONAZOLE AND FLUCONAZOLE ENHANCED WITH SILVER METAL COLLOID CREAMS: A 3² FACTORIAL DESIGN OPTIMIZATION APPROACH (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Antifungal resistance remains a critical health challenge within dermatology and pharmaceutical research. This study aimed to enhance antifungal creams by investigating the effectiveness of fluconazole (FLZ) and fluconazole combined with silver metal colloid (FLZ-AgMC). Employing a 3² factorial design, systematic exploration was conducted to assess the influence of metal colloid concentration and stearic acid content on crucial cream attributes: viscosity, spreadability, and zone of inhibition ratio. Viscosity ranged from 56132 to 58700 cP, spreadability from 28.7 to 27.8 gm.cm/sec, and the zone of inhibition increased with metal colloid concentration. Optimized cream formulations were identified using Stat-Ease Design Expert version 7. Various FLZ and AgMC concentrations were evaluated for antifungal activity against Candida albicans, with FLZ-AgMC exhibiting significantly enhanced efficacy, as indicated by a larger inhibition zone compared to FLZ alone. The inhibitory zone ratio demonstrated a 35 to 40% improvement, indicating enhanced fungal growth inhibition. Skin permeation and ex-vivo studies confirmed that the optimized Fluconazole formulation followed the Higuchi Model (R2 = 0.9847). Silver metal colloid-containing formulations demonstrated superior antifungal efficacy against C. albicans. The impact of silver metal colloid and stearic acid on viscosity and spreadability was established, revealing key factors influencing the cream’s physical properties. This optimization approach highlights the potential for innovative antifungal formulations, contributing to improved patient care, user acceptability, and clinical application.